1999
DOI: 10.1159/000018233
|View full text |Cite
|
Sign up to set email alerts
|

Interdigital Intertrigo of the Feet due to Therapy-Resistant Fusarium solani

Abstract: We report a case of bilateral intertrigo of the third and fourth interdigital spaces of the feet in a 34-year-old immunocompetent Senegalese male. A diagnosis of Fusarium solani infection was made. Systemic and topical therapy with terbinafine led to clinical but not mycological recovery. As this mould is potentially dangerous for immunodepressed subjects, early diagnosis and rigorous follow-up of skin diseases caused by this agent are advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Firstly, however, it must be stated that the degree of interest in this matter naturally depends on whether any treatment issue depends on fungal identification. Some controversy attends this topic, but it is certainly well established that fungi in the order Microascales, including the nail-infecting Scopulariopsis species, and fungi in the order Hypocreales, including the nail-infecting Fusarium and Acremonium species, show distinctive and often (although not always) unpromising responses in vitro to currently used oral antifungals, including fluconazole, griseofulvin, terbinafine, and itraconazole (2,5,8,16,24,27,29,33,39,41). Although the situation in vivo may be more complex, as is suggested by apparent cure of some Fusarium and Scopulariopsis onychomycosis by itraconazole or terbinafine therapy (8,14,28,40), there appears to be good prima facie justification for a dermatologist wanting to know whether his or her patient is truly infected by one of these normally drug resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, however, it must be stated that the degree of interest in this matter naturally depends on whether any treatment issue depends on fungal identification. Some controversy attends this topic, but it is certainly well established that fungi in the order Microascales, including the nail-infecting Scopulariopsis species, and fungi in the order Hypocreales, including the nail-infecting Fusarium and Acremonium species, show distinctive and often (although not always) unpromising responses in vitro to currently used oral antifungals, including fluconazole, griseofulvin, terbinafine, and itraconazole (2,5,8,16,24,27,29,33,39,41). Although the situation in vivo may be more complex, as is suggested by apparent cure of some Fusarium and Scopulariopsis onychomycosis by itraconazole or terbinafine therapy (8,14,28,40), there appears to be good prima facie justification for a dermatologist wanting to know whether his or her patient is truly infected by one of these normally drug resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Most intriguingly, an unusual type of intertrigo, an infection almost never definitively shown to be caused by any fungi other than dermatophytes and Scytalidium species (older literature contains many inadequately substantiated case reports in which other species are mentioned, probably based on misattribution of the infection to contaminants isolated when a causal dermatophyte failed to grow), appears to be caused exclusively by opportunistic members of the F. solani and Gibberella clades. F. solani has been reported from two well-documented cases of this intertrigo (6,49). The cause of a third such case, probably valid but not as rigorously documented (the putative agent was not reisolated on successive occasions in order to rule out dermatophytosis), was ascribed to the invalid name Cephalosporium keratoplasticum Morikawa by Harada and Usui (20); the case isolate, preserved as CBS 490.63, is F. solani and was sequenced in the present study.…”
Section: Fig 1 Phylogenetic Relationships Within the Genusmentioning
confidence: 99%
“…(27) that can be clearly recognized from its published description and photos as F. lichenicola have been well documented as causes of similar cases of intertrigo. Three of these fusarial intertrigo cases were described from patients of recent West African origin living in Europe (27,48,49), while in a fourth case (6), the patient's geographic history was not discussed, but he was described both as a French resident and as a "practicing Muslim. .…”
Section: Fig 1 Phylogenetic Relationships Within the Genusmentioning
confidence: 99%
“…is a rare infection causing interdigital foot lesions (Romano and Gianni, 2002). Romano et al (Romano et al , 1998b, Romanno et al , 1999c) found that only four cases of interdigital intertrigo resulting from Fusarium spp . have been reported.…”
Section: Discussionmentioning
confidence: 99%